Efforts To Increase Students Interest In Further Studies Socialization Of The UIN Sultanah Nahrasiyah Campus Excellence Program - Asra; Muslina, Muslina; Maulina, Isra; Sufrizal, Sufrizal; Zulfikar, Zulfikar; Anwar, Nur (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2025)
A school is a formal educational institution or service aimed at developing students potential. Education is a conscious and planned effort to create a learning atmosphere and process so that students actively develop their potential to possess spiritual and religious strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, society, the nation, and the state. In era of globalization, learning is no longer limited to school, further study at university is also necessary. Further study is one way to improve human resources within an institution. By continuing their studies, a person can broaden their knowledge and gain new experiences, which then become provisions for advancing the institution where they work. Further study demonstrates a person's dedication to improving the quality and credibility of an institution. In this effort to improve the quality of human resources, campus outreach is needed to help students choose the campus and study program of interest. The outreach activities carried out by the UIN Sultanah Nahrasiyah campus outreach team involved direct interaction and outreach at SMA/MAN in Pidie Jaya. Overall, students were very enthusiastic about this outreach and increased their interest in further study in their desired study program on campus. Ongoing outreach will continue as part of the campus development strategy. The importance of this outreach extends beyond new student registration to developing collaborative networks with schools.